Research on the Natural Movement of Population in the South-Mountain Region - Camelia Maria PROCOP; Eduard Alexandru DUMITRU; Mihnea-Iulian VASILIU; Ana Ruxandra MICU (Communications of International Proceedings, 2020)
This paper refers to the current situation of the population in the South-Muntenia Region, highlighting the social situation of this region, as well as the factors that influence the evolution of the population. At the national level, there is a demographic decline, due in particular to the low birth rate in comparison with the death rate, but also to the migration of the population, to areas with a higher standard of living. This is analyzed, it is obvious for the situation of its rural area in the South-Muntenia region in the direction of the marked demographic decline, in the situation of care in this regard regarding the need to take measures. Also regarding the works and encourages mentions or a series of measures designed to stop this demographic decline recorded in the analyzed region. Unfortunately, the low birth rate correlated with the high mortality recorded in this area, reveals gloomy prospects regarding the evolution of the countryside in the South-Muntenia region.
Keywords: Rural Development; Demography; Population.